2020
DOI: 10.3389/fpls.2020.559070
|View full text |Cite
|
Sign up to set email alerts
|

Redox Status, JA and ET Signaling Pathway Regulating Responses to Botrytis cinerea Infection Between the Resistant Cucumber Genotype and Its Susceptible Mutant

Abstract: Botrytis cinerea is an important necrotrophic fungal pathogen with a broad host range and the ability to causing great economic losses in cucumber. However, the resistance mechanism against this pathogen in cucumber was not well understood. In this study, the microscopic observation of the spore growth, redox status measurements and transcriptome analysis were carried out after Botrytis cinerea infection in the resistant genotype No.26 and its susceptible mutant 26M. Results revealed shorter hypha, lower rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 99 publications
1
11
0
Order By: Relevance
“…In grapes, low constitutive ROS production was also associated with a high level of resistance to B. cinerea ( Rahman et al, 2020 ). Similar results were found in cucumber, where a lower accumulation of H 2 O 2 , O 2 − was found in a resistant genotype compared to a susceptible genotype after B. cinerea inoculation ( Yang et al, 2020 ). In this study, we observed that T3 leaves have a higher level of H 2 O 2 compared to K1 and that there was a significant positive correlation between H 2 O 2 content and symptom development (i.e., Lesion area) for both genotypes ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 77%
“…In grapes, low constitutive ROS production was also associated with a high level of resistance to B. cinerea ( Rahman et al, 2020 ). Similar results were found in cucumber, where a lower accumulation of H 2 O 2 , O 2 − was found in a resistant genotype compared to a susceptible genotype after B. cinerea inoculation ( Yang et al, 2020 ). In this study, we observed that T3 leaves have a higher level of H 2 O 2 compared to K1 and that there was a significant positive correlation between H 2 O 2 content and symptom development (i.e., Lesion area) for both genotypes ( Figure 5 ).…”
Section: Discussionsupporting
confidence: 77%
“…For example, the Csa5G223070 gene, encoding WRKY transcription factor, was up-regulated in both lines and time points, with a significantly higher expression level at 1 dpi in the resistant Gy14 line (Figure 5, Supplementary Table S2). Yang et al [44] reported that three WRKY genes, including Csa5G223070, were highly induced in resistant line No.26 after B. cinerea infection. Expression of this WRKY gene increased also during defense responses against powdery mildew [24] and P. melonis infections [21].…”
Section: Discussionmentioning
confidence: 99%
“…JA and its derivatives, including MeJA, jasmonoyl isoleucine (JA-Ile), cis-12-oxophytodienoic acid (OPDA), and cis-jasmone, are produced by both healthy and wounded plants [38][39][40]. In addition, these hormones accumulate to high levels in response to a wide variety of external stimuli, such as herbivorous insects, necrotrophic pathogens, and other biotic/abiotic stresses [41,42]. JA and its derivatives, most notably JA-Ile, regulate a wide spectrum of plant physiological processes, such as root growth inhibition, plant development, pathogen resistance, male sterility, trichome initiation, and anthocyanin accumulation, by regulating diverse sets of intracellular signaling pathways and reprogramming downstream target genes [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these hormones accumulate to high levels in response to a wide variety of external stimuli, such as herbivorous insects, necrotrophic pathogens, and other biotic/abiotic stresses [41,42]. JA and its derivatives, most notably JA-Ile, regulate a wide spectrum of plant physiological processes, such as root growth inhibition, plant development, pathogen resistance, male sterility, trichome initiation, and anthocyanin accumulation, by regulating diverse sets of intracellular signaling pathways and reprogramming downstream target genes [42,43]. The molecular basis of JA signaling was initially uncovered through the characterization of the SCF COI1 protein [44].…”
Section: Discussionmentioning
confidence: 99%